The (Im)Possibility of Interrupting Midwest Nice in a Predominantly White, Small-Town School District - Emily O. Miller (MDPI AG, 2024)
As school and district leaders are confronted with explicit opposition to racial equity and inclusion policies and practices, they also continue to contend with Nice resistance. In this ethnographic case study, I draw on interviews with teachers and administrators as well as observations of meetings and professional learning sessions to explore how educational leaders in a predominantly white, small, Midwestern town navigated a culture of Niceness characterized by good intentions, comfort, and avoiding conflict. Though most educators said they supported equity and inclusion, they resisted the administration and the policies and practices administrators implemented. Leaders challenged the culture of Niceness in the school district by focusing on impacts, pushing teachers to do things they were not comfortable with, and having direct conversations. Ultimately, several administrators left the district, and some equity and inclusion efforts were stalled or rolled back. Based on the findings of this study, I conclude that it is difficult to interrupt Niceness in the interest of advancing racial equity and inclusion.